1992
DOI: 10.1136/bmj.305.6868.1561
|View full text |Cite
|
Sign up to set email alerts
|

Noise and the classical musician.

Abstract: Objectives-To test the hypothesis that noise exposure may cause hearing loss in classical musicians.Design-Comparison of hearing levels between two risk groups identified during the study by measuring sound levels.Setting-Symphony orchestra and occupational health department in the west Midlands. Main outcome measures-Hearing level as measured by clinical pure tone audiometry.Results-Trumpet and piccolo players received a noise dose of 160% and 124%, respectively, over mean levels during part of the study. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
8

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 3 publications
3
30
0
8
Order By: Relevance
“…Em relação ao dano auditivo provocado pela exposição à música, observou-se neste estudo que, dentre os 50 sujeitos que realizaram a audiometria tonal, 32% apresentaram alteração auditiva (Tabela 3) e que os casos que possuíam audiogramas com características de PAIR (24% dos sujeitos avaliados) aumentavam conforme o tempo de atuação na banda, evidenciando o risco da música executada em intensidade elevada para a audição. Em estudos com orquestras sinfônicas, os autores também sugerem relação entre o tempo de atuação como músico e a alteração auditiva, porém em menor impacto do que trabalhadores expostos ao ruído intenso nas indústrias (25)(26) ; assim, os autores sugeriram que a música é prejudicial à audição, mas não tão agressiva como o ruído dos ambientes industriais. Em outro estudo realizado com músicos da Banda Militar da Base Aérea de Santa Maria não foram encontrados indivíduos com alterações auditivas, mas com presença de entalhe acústico nas freqüências de 3000, 4000 e/ou 6000 Hz em 50% deles, sendo que o tempo de atuação na banda do total dos sujeitos variou de cinco a 26 anos (12) .…”
Section: Discussionunclassified
“…Em relação ao dano auditivo provocado pela exposição à música, observou-se neste estudo que, dentre os 50 sujeitos que realizaram a audiometria tonal, 32% apresentaram alteração auditiva (Tabela 3) e que os casos que possuíam audiogramas com características de PAIR (24% dos sujeitos avaliados) aumentavam conforme o tempo de atuação na banda, evidenciando o risco da música executada em intensidade elevada para a audição. Em estudos com orquestras sinfônicas, os autores também sugerem relação entre o tempo de atuação como músico e a alteração auditiva, porém em menor impacto do que trabalhadores expostos ao ruído intenso nas indústrias (25)(26) ; assim, os autores sugeriram que a música é prejudicial à audição, mas não tão agressiva como o ruído dos ambientes industriais. Em outro estudo realizado com músicos da Banda Militar da Base Aérea de Santa Maria não foram encontrados indivíduos com alterações auditivas, mas com presença de entalhe acústico nas freqüências de 3000, 4000 e/ou 6000 Hz em 50% deles, sendo que o tempo de atuação na banda do total dos sujeitos variou de cinco a 26 anos (12) .…”
Section: Discussionunclassified
“…In a study with 329 music students (aged between 18 and 25 years), there was no evidence of hearing loss, but of acoustic notch in 45% of the students (78% of them presented acoustic notch in 6,000 Hz and 22% in 4,000 Hz) (17) . Other studies also found hearing disorders among musicians, but not at high proportions; however, they observed acoustic notch in the frequencies of 4,000 or 6,000 Hz, more often than expected when compared to non-musicians, considering the same age and gender (1,3,8,9,(18)(19)(20) . It was observed that hearing thresholds of musicians got worse with time of exposure to music and, in this assessed group, the longer the time of exposure (in years), the worse the hearing thresholds found in high-frequency audiometry (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed with classical musicians show that the levels of sound pressure in orchestras during rehearsals or performances may range from 77 to 93 dB(A), reaching peaks of 110 dB(A) (1)(2)(3) . Researchers throughout the world described hearing disorders caused by exposure to music, such as hearing impairment or differences in hearing thresholds, not necessarily as disorders related to hearing loss, especially in high frequencies (3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…No caso do trabalho com os instrumentistas, os dados da literatura apontam principalmente para prejuízos advindos do ambiente físico, associados à perda auditiva induzida pelo ruído (PAIR) (McBRIDE et al, 1992;MARCHIORI;MELO, 2001;MENDES;KOEMLER;ASSENCIO-FERREIRA, 2002;MILLER;STEWART;LEHMAN, 2007;AMORIM et al, 2008;MARTINS et al, 2008), e das adequações ergonômicas e de equipamentos como, por exemplo, a queixeira e a espaleira (BRANDFONBRENER, 1989;LEVY et al, 1992;STEINMETZ;SEIDEL;NIEMIER, 2008).…”
Section: Pontos]unclassified